Representasi Kapitalisme dalam Iklan Digital dan Dampaknya terhadap Gaya Hidup - Rafi Rivaldi Akbar; Dicky Pastyo; Eko Purwanto (Mellbaou Publisher, 2025)
This study aims to examine the representation of capitalist ideology in digital advertising and its impact on shaping consumer lifestyles in society. Employing a qualitative approach with a literature review method, this research analyzes various sources to identify how digital advertisements convey capitalist values through narratives, visuals, and data-driven personalization. The findings reveal that digital advertising not only promotes products but also actively constructs an artificial ideal lifestyle that is materialistic, individualistic, and status-oriented. Social media and algorithms play a significant role in amplifying the psychological effects of advertising, particularly among young generations, leading to excessive consumer culture and potential negative psychological impacts. This study concludes that critical media literacy is a crucial solution for raising awareness and mitigating the adverse effects of digital advertising